2021
DOI: 10.1136/bmjpo-2021-001159
|View full text |Cite
|
Sign up to set email alerts
|

Structures of paediatric pain management: a PERUKI service evaluation study

Abstract: BackgroundPain is very common in childhood emergency department (ED) attendances, but is under-recognised and undertreated. Sequential national paediatric analgesia audits demonstrate suboptimal outcomes in several domains. The Donabedian framework examines the structures, processes and outcomes to evaluate quality of care. To date there has been no network-level exploration of structures supporting analgesic practices or attempts to address failure to attain national standards.ObjectiveTo benchmark current va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…This suggests a lack of uniform assertive ED pain management across the network, with the source issue likely to be related to knowledge translation and culture 2 6. A previous PERUKI study identified that training was included in induction/orientation in 24 sites (63%), professional development in 16 sites (42%), and pain/analgesia competencies were mandatory in 15 sites (39%),15 implying that pain education is a low priority for over 50% of responding institutions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This suggests a lack of uniform assertive ED pain management across the network, with the source issue likely to be related to knowledge translation and culture 2 6. A previous PERUKI study identified that training was included in induction/orientation in 24 sites (63%), professional development in 16 sites (42%), and pain/analgesia competencies were mandatory in 15 sites (39%),15 implying that pain education is a low priority for over 50% of responding institutions.…”
Section: Discussionmentioning
confidence: 99%
“…We have identified fundamental gaps in structures and processes that have resulted in the suboptimal outcomes. A strength of this study is that we have paired this study to the related structures 15. This study included patients aged from birth to 15 years (prior to their 16th birthday), with a range of nociceptive injuries, allowing for generalisable conclusions about pain practices for almost 4000 paediatric ED patient episodes related to minor injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2017 PERUKI survey, exploring structure supporting analgesic practices, described delivery of PPS in 13 (37%) of the 40 PERUKI member sites at the time. 13 In three years there has been a relative increase of 45%. However, despite wide use of PPS, we have found wide variability in agents and practices.…”
Section: Discussionmentioning
confidence: 99%